Extrahepatic metastasectomy for hepatocellular carcinoma: Predictors of long‐term survival. Issue 4 (22nd June 2016) - Berger, Yaniv; Spivack, John H.; Heskel, Marina; Aycart, Samantha N.; Labow, Daniel M.; Sarpel, Umut
Abstract : Introduction: We report our institutional experience with extrahepatic metastasectomy (EM) in a cohort of hepatocellular carcinoma (HCC) patients with focus on predictors of survival. Methods: All patients diagnosed with metastatic HCC from 2001 to 2014 were retrospectively reviewed to identify those who underwent EM with therapeutic intent. Associations among multiple clinicopathological variables and survival after EM were analyzed by univariate and multivariate analyses. Results: Out of 440 metastatic HCC cases, we identified 85 patients (mean age 58.8 ± 11.7 years, 81.2% males) who underwent lung (n = 36), peritoneal (n = 22), lymph node (n = 19), musculoskeletal (n = 18), and adrenal (n = 9) metastasectomy. Most patients (84.7%) underwent metachronous EM following primary liver resection or transplantation. The median follow‐up period was 20.9 months, during which 55 patients (64.7%) died. The 1‐/2‐/5‐year overall survival rates after EM were 77.4, 53.1, and 25.1%, respectively. On multivariate analysis, number of metastases resected >2 correlated independently with poor survival (HR = 2.058, P  = 0.0099). EM patients had superior median survival compared to all (n = 194) metastatic HCC patients treated with sorafenib without EM during the study period (27.2 vs. 7.4 months, P  < 0.001). Conclusion: Long‐term survival may be achieved in highly selected HCC patients following EM. The presence of greater than two extrahepatic lesions correlates independently with poor survival. J. Surg. Oncol. 2016;114:469–474 . © 2016 Wiley Periodicals, Inc.